Promoción y prevención en salud bucodental en madres gestantes y lactantes que asisten a la fundación médico preventiva - Santiago Pinto, Juliany Paola (Universidad Antonio Nariño, 2021)
Dental caries remains a public health problem in many countries and can be prevented through timely promotion and prevention measures, based on the oral health knowledge that women acquire during pregnancy. OBJECTIVE: Determine the level of knowledge about promotion and prevention activities in oral health in pregnant and lactating mothers belonging to the Preventive Medical Foundation and Bibliographic Review. MATERIALS AND METHODS: Descriptive, cross-sectional research in which 20 questionnaires were carried out to evaluate the level of knowledge in oral health practices in pregnant and lactating mothers between the ages of 18 and 45. After obtaining consent, theoretical and practical training was given on oral health education by stages, chronology of tooth eruption and preventive measures in children under the age of 6. Due to the health circumstances of the covid-19 contingency, and the restrictive measures, the research was complemented by a bibliographic review incorporating ten indexed scientific articles. RESULTS: A convenience sample of 20 participants was obtained, in which the general percentage of the level of knowledge was 55.65%, mothers with a lower level of education obtained a percentage of 36.9% compared to mothers with a professional educational level who obtained a percentage of 57%. Participants from lower strata obtained less than 55%, while those from stratum 3 obtained 73.5%. CONCLUSION: Most of the respondents have regular knowledge; finding a direct relationship between socioeconomic level and level of knowledge, however no significant findings were found that indicate that a level of academic training directly influences education in oral health.